Model of Competency Formation in Future Physical Education Teachers - Shermatov M.N. (Web of Journals Publishing, 2023)
In this article, the preparation of future teachers for professional activities, comprehensive social life, including the issue of assessing the educational results of students and assessing the educational process in research using monitoring methods, was considered as an indispensable condition for improvement.
Keywords: Observation, repetition, implementation and systematization, analysis and evaluation, competence, acmeological, cluster.